Multiple ecological processes underpin the eruptive dynamics of small mammals: House mice in a semi‐arid agricultural environment. Issue 7 (5th March 2020) - Brown, Peter R.; Arthur, Anthony D.; Jones, Dean A.; Davies, Micah J.; Grice, David; Pech, Roger P.
Abstract: Mouse plagues are a regular feature of grain‐growing regions, particularly in southern and eastern Australia, yet it is not clear what role various ecological processes play in the eruptive dynamics generating these outbreaks. This research was designed to assess the impact of adding food, water, and cover in all combinations on breeding performance, abundance, and survival of mouse populations on a typical cereal growing farm in northwestern Victoria. Supplementary food, water, and cover were applied in a 2 × 2 × 2 factorial design to 240 m sections of internal fence lines between wheat or barley crops and stubble/pasture fields over an 11‐month period to assess the impact on mouse populations. We confirmed that mice were eating the additional food and were accessing the water provided. We did not generate an outbreak of mice, but there were some significant effects from the experimental treatments. Additional food increased population size twofold and improved apparent survival. Both water and cover improved breeding performance. Food and cover increased apparent survival. Our findings confirm that access to food, water, and cover are necessary for outbreaks, but are not sufficient. There remain additional factors that are important in generating mouse plagues, particularly in a climatically variable agricultural environment. Abstract : The ecological processes that underpin the eruptive dynamics of small mammals were manipulated in a semi‐arid agricultural environment through provision of supplementary food, water, and cover to try and generate an outbreak of the feral house mouse. Additional food increased population size twofold and improved apparent survival, both water and cover improved breeding performance, and food and cover increased apparent survival, but we did not generate an outbreak of mice. Our findings confirm that access to food, water, and cover are necessary for outbreaks, but are not sufficient; there remain additional factors that are important in generating mouse plagues, particularly in a climatically variable agricultural environment.